2017
DOI: 10.1186/s13053-017-0077-6
|View full text |Cite
|
Sign up to set email alerts
|

Emotional impact on the results of BRCA1 and BRCA2 genetic test: an observational retrospective study

Abstract: BackgroundBRCA1 and BRCA2 mutations are associated with a higher risk of breast and ovarian tumors. This study evaluated the emotional states of women 1 month after having received the results of the genetic test and assessed eventual associations with the type of outcome, personal/familiar disease history and major socio-demographic variables.MethodsThe study, an observational retrospective one, involved 91 women, evaluated 1 month after receiving their results. Patients were administered the Hospital Anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…In general, I-PACH scores were negligibly associated with background characteristics, except for a tendency to decrease with age. While this latter result is consistent with findings by Ballatore et al (2020), the former replicates those already reported by Mella et al (2017). Notably, all scores were significantly associated with a positive answer to the question about the wish to speak with a psychologist in addition to the clinical geneticist/ genetic counselor, albeit weakly.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In general, I-PACH scores were negligibly associated with background characteristics, except for a tendency to decrease with age. While this latter result is consistent with findings by Ballatore et al (2020), the former replicates those already reported by Mella et al (2017). Notably, all scores were significantly associated with a positive answer to the question about the wish to speak with a psychologist in addition to the clinical geneticist/ genetic counselor, albeit weakly.…”
Section: Discussionsupporting
confidence: 90%
“…However, the possible negative consequences of oncogenetic counseling on psychological wellbeing of Italian counselees and the need of a psycho-oncologist in a multidisciplinary team have been pointed out more than a decade ago (e.g., Condello et al, 2007 ; Caruso et al, 2008 ). Recent studies carried out in Italy have shown that ex-patients and affected patients, especially if females and younger, tend to report higher levels of anxiety, depression, negative mood, and genetic risk perception, and lower levels of quality of life and wellbeing than healthy counselees, and thus may be at risk of psychological discomfort during the counseling process (e.g., Cicero et al, 2017 ; Mella et al, 2017 ; Di Mattei et al, 2018 ; Ballatore et al, 2020 ). Therefore, identifying counselees’ personal and psychosocial needs before and after genetic testing could help Italian practitioners target those individuals who are most likely to seek and to use psychological service ( Maheu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study by Walker et al, the point prevalence for depression in breast cancer patients was 9.3% (95% CI, 8.7-10.0%) (38), whereas the point prevalence for major depression in our sample of mutation carriers was 16.9% (n = 13). Mella et al observed even higher anxiety and depression levels in BRCA1 or BRCA2 mutation carriers without cancer than in diseased individuals (39). These research ndings demonstrate that the detection of a mutation can cause cancer fear and lead to psychological distress (8,36).…”
Section: Discussionmentioning
confidence: 83%
“…Nevertheless, most mutation carriers were very satis ed with the decision of undergoing genetic testing. Another limiting factor in our analysis was that men and women were included in the study population, however, middle-aged women were overrepresented, equivalent to previous studies on genetic testing (39,43). This could also have led to a potential underrepresentation of gender-based aspects.…”
Section: Discussionmentioning
confidence: 95%
“…Although geneticists are aware of such issues, participants’ declarations tended to show that the distress is generally much deeper than expected. The duration of this trauma has been discussed, some authors considering it to be transient [21, 22] while others report high level of distress, anxiety, depression and/or anger still 1 month after announcement [23, 24], in particular in young counselees from mutated families coming for a targeted test. This was the case of our participants.…”
Section: Discussionmentioning
confidence: 99%